Vulvovaginal atrophy: modern approaches to diagnostics and management - V. H. Siusiuka; N. V. Avramenko; M. I. Pavliuchenko; M. Yu. Serhiienko; A. O. Kniazieva (Zaporožskij Medicinskij Žurnal)
The aim of the review is to analyze the latest data on the current state of diagnosis and management of a common benign vulvar and vaginal disease in postmenopausal women – atrophic vulvovaginitis.